Dopamine agonist increases risk taking but blunts reward-related brain activity. - Jordi Riba; Ulrike M Krämer; Marcus Heldmann; Sylvia Richter; Thomas F Münte (PLoS ONE, 2008)
The use of D2/D3 dopaminergic agonists in Parkinson's disease (PD) may lead to pathological gambling. In a placebo-controlled double-blind study in healthy volunteers, we observed riskier choices in a lottery task after administration of the D3 receptor-preferring agonist pramipexole thus mimicking risk-taking behavior in PD. Moreover, we demonstrate decreased activation in the rostral basal ganglia and midbrain, key structures of the reward system, following unexpected high gains and therefore propose that pathological gambling in PD results from the need to seek higher rewards to overcome the blunted response in this system.